Mapeamento 3D de descontinuidades sísmicas na província Borborema com funções de receptor - Almeida, Ygor Bastos Mesquita Minora de (2014)
The crustal architecture of the Borborema Province was investigated through migration and stacking of receiver functions (phase-weighted-stack). The stacks were developed from teleseismic -waves recorded at 64 seismological stations distributed throughout Northeast Brazil, after applying a number of modifications to the stacking algorithm that corrected inconsistencies in the original algorithm and improved its computational efficiency. The Borborema Province is the westernmost portion of a Neoproterozoic orogen that experienced extension in the Mesozoic, leading to the formation of a number of intracontinental rift basins and, eventually, to the continental drift. The Cenozoic was marked by topographic uplift of the Province, perhaps related to coeval episodes of volcanism, which resulted in the formation of the Borborema Plateau. Due to limited understanding of the crustal architecture of the Province, the causal relationships between surface topography, Mesozoic extension, and Cenozoic uplift are poorly understood. The receiver function stacks highlight conversions from the crust-mantle boundary that demonstrate a thick crust between 36 and 40 km in the southern Plateau, and crust between 30 and 32 km in the regions around, including the northern Plateau. The receiver function stacks also revealed the presence of a discontinuity between 9 and 18 km depth that tends to fade away towards the southern Plateau as the crust thickens. It is argued that the thin crust in the Borborema Province is the result of crustal stretching during Mesozoic times, and that the intracrustal discontinuity marks the location of a lowangle detachment zone that accommodated extension within the crust. The thick crust in the southern Plateau would then be a rheologically strong block that resisted deformation during the Mesozoic, while the thin crust beneath the northern Plateau would be a portion of a formerly depressed crust that experienced uplifted during the Cenozoic.